Combined Effect of Moringa oleifera and Ionizing Radiation on Survival and Metastatic Activity of Pancreatic Cancer Cells. (March 2019) - Hagoel, Lior; Vexler, Akiva; Kalich-Philosoph, Lital; Earon, Gideon; Ron, Ilan; Shtabsky, Alex; Marmor, Silvia; Lev-Ari, Shahar
Background: Radiotherapy is one of the main treatments for malignancies. Radioresistance is a major obstacle in this treatment, calling for new treatments to improve radiotherapy outcome. Herbal medicine has low toxicity and could be a source for new radio-enhancing agents. Moringa oleifera (moringa) is a well-known medicinal plant with antiproliferative and antimetastatic properties. Possible mechanisms of moringa anticancer activity may be related to the expression of PARP-1, Bcl-2, COX-2, p65, p-IκB-a, and others.Purpose: The aims of the present study were to investigate effect of moringa alone and combined with radiation on survival and metastatic activity of pancreatic cancer cells and on tumor growth.Methods and Results: The combination of moringa and radiation significantly inhibited PANC-1 cell survival in a dose-dependent manner, as tested by clonogenic and XTT assays. Moreover, standard transwell cell migration/invasion assays demonstrated reduced metastatic activity of these cells. Pyruvate mitigated the inhibitory effect of combined treatment on cell survival. Flow cytometry of moringa-treated cells revealed induction of apoptosis. Western blot analysis found that the combined treatment decreased expression of the pro-apoptotic protein Bcl-2, and downregulated the key component of DNA repair pathways PARP-1 and the NF-κB-related proteins IκB-α, p65-subunit, and COX-2. Moringa significantly inhibited growth of subcutaneous tumors generated by PANC-1 cells in nude mice. Immunohistochemical analysis demonstrated moringa's antiproliferative and antiangiogenic effects.Conclusions: Moringa decreased pancreatic cancer cell survival and metastatic activity and significantly inhibited tumor growth. The combination of moringa plus radiation resulted in an additional inhibitory effect that provided the rationale for further investigation of this combination as a novel strategy to overcome pancreatic cancer cell radioresistance.